Accessibility to primary health care services in the state of Goiás - Juliana Pires Ribeiro; Samira Nascimento Mamed; Marta Rovery Souza; Márcia Maria de Souza; Claci Fátima Weirich Rosso (Universidade Federal de Goias, 2015)
The objective of this study was to evaluate accessibility to primary health care services in the state of Goiás. A descriptive cross-sectional study was conducted based on secondary data from the National Program to Improve Access to and Quality of Primary Health Care. The study sample was composed of health professionals from 1,216 primary health care units. Results showed that 68.5% of the health units miss a screening room, thus considerably damaging prompt decision-making by professionals. The lack of medical offices in 2% of the sites hinders the primary health care services accessibility in Goiás. As regards opening hours and work shifts, 86% of the units are open five days a week in eight-hour shifts, which does not favor accessibility for users. This study confirms the lack of accessibility to health services and the need for additional investments to strengthen primary health care.